When the Place Matters: Moving the Classroom Into a Museum to Re-design a Public Space - Barzanò, Giovanna; Amenduni, Francesca; Cutello, Giancarlo; Lissoni, Maria; Pecorelli, Cecilia; Quarta, Rossana; Raffio, Lorenzo; Regazzini, Claudia; Zacchilli, Elena; Ligorio, Maria Beatrice (Frontiers in Psychology, 2020)
In this case-report we describe an experience where alternative places – rather than the classroom – are exploited to implement learning processes. We maintain that this experience is a good example of materiality because it focuses on a project where students had the opportunity to re-design a public space. To this aim, various objects and tools are used to support discussions and exchanges with new stakeholders. Our theoretical vision combines Piaget’s and Vygotsky’s tradition with an innovative framework called the Trialogical Learning Approach (TLA). From such theoretical background an idea of materiality emerges, that refers to material in combination with the social relationships developed around the material. Our case-report concerns a participatory project run by Rete Dialogues, a national school network focusing on global citizenship education. Our research question is: how can this project highlight the connection between the TLA and socio-materiality? Since 2017, around 200 students (age 7-16) and 20 teachers from different schools have been engaged in tackling the degradation of an important square in Rome. The project – “Dialogues in the Square” (DiS) was developed with several stakeholders that contributed to the understanding of critical issues influencing the maintenance of the square, in the perspective of planning, and possibly implementing improvements proposed by students. Crucial is the cooperation with two important urban art projects: i) the pilot-project MACRO-ASILO, run by the MACRO museum in Rome and aimed at connecting the world of art with the city life; ii) the “building sites” of the Rome Rebirth Forum, inspired by the world-known artist Michelangelo Pistoletto’s “third paradise” methodology, that encourages responsibility and action taking on sustainability through art. Drawing on data collected through direct observations and video recordings, we aim to show and make sense of the connection between the TLA and socio-materiality, highlighting three key elements: the flexible use of mediation tools, the overcoming of the dichotomy between individual and collective learning through reflection, and the re-shaping of social practices.